PENGARUH PROFITABILITAS DAN NILAI PASAR TERHADAP HARGA SAHAM SYARIAH PADA PERUSAHAAN YANG TERDAFTAR DI JAKARTA ISLAMIC INDEX (JII) TAHUN 2011-2013 - Asnaini, Asnaini; Elvira, Rini; Yuningsih, Ayu (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2016)
This research aimed to investigate the effect of profitability ratio (ROA,ROE) and market value ratio (EPS) on sharia stock price at companies listed in Jakarta Islamic Index (JII). This research was applied research which is assosiative quantitative. The population of this research was all of companies listed in Jakarta Islamic Index (JII) in 2011-2013 period. In selecting the sample was done by purposive sampling technique. The number of samples were 24 companies listed in Jakarta Islamic Index (JII) within 3 years a row. This research used multiple regression linier techniques in hypothesis testing. Research result showed that Return On Assets (ROA), Return On Equity (ROE), and Earning Per Share (EPS) simultaneously have a possitive and significant effect on sharia stock price. While, the effect was partially different, Return On Assets (ROA) and Return On Equity (ROE) had not possitive and significant effect on sharia stock price. While Earning Per Share (EPS) has possitive and significant effect on sharia stock price.Key Words:  Sharia Stock, Sharia Stock Price, ROA, ROE, EPS